Energy-Water Nexus - Colmenar Santos, Antonio; Borge Diez, David; Rosales Asensio, Enrique (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Water is necessary to produce energy, and energy is required to pump, treat, and transport water. The energy-water nexus examines the interactions between these two inextricably linked elements. This Special Issue aims to explore a single "system of systems" for the integration of energy systems. This approach considers the relationships between electricity, thermal, and fuel systems; and data and information networks in order to ensure optimal integration and interoperability across the entire spectrum of the energy system. This framework for the integration of energy systems can be adapted to evaluate the interactions between energy and water. This Special Issue focuses on the analysis of water interactions with and dependencies on the dynamics of the electricity sector and the transport sector